Gender, Social Bond, and Academic Cheating in Japan - Fukushima, Miyuki (2012)
There is evidence that females are less likely to cheat than males on college campuses. A frequently offered but still untested explanation is that females, with a stronger sense of responsibility for the maintenance of social relationships, tend to develop a stronger bond to a conventional society—a key explanatory concept in Hirschi’s (1969) social control theory. With academic cheating as the dependent variable, we test the hypotheses that the four elements of social bond are the intervening variables linking gender to such dishonesty among Japanese students who, due to their stronger orientation toward masculinity on Hofstede’s (1980) scale of gender role separation, are subject to more gender distinct socialization, leading to greater gender differences in the strength of social bond than those previously reported in the United States. The analysis provides rather limited support for the theory, most of which is due to the stronger belief in the legitimacy of societal rules among the females